PENGARUH STOCK SPLIT DAN EARNING PER SHARE TERHADAP HARGA SAHAM (Studi Kasus Pada Perusahaan Manufaktur Di Bursa Efek Indonesia) - Mulyadi Mulyadi; Budi Wahono; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2018)
Abtraksi This study aims to determine and analyze the effect of Stock Split, Earning Per Share on Stock Prices. The technique used in sampling is purposive sampling technique where the technique of determining the sample with consideration of certain criteria. The analysis technique used is descriptive quantitative using multiple linear regression analysis and also through t test using the SPSS program. Based on the results of partial data analysis shows that Stock Split has a negative effect not significant on stock prices, Earning Per Share has a positive and significant effect on stock prices. Keywords: Stock Split, Earning Per Share and Share Prices